Analytical and CFD study of the influence of control parameters on the maximum efficiency of a hydro-power conversion system based on vortex-induced vibrations. (August 2020) - Lefebure, David; Dellinger, Nicolas; François, Pierre; Mosé, Robert
Abstract: An increasing demand for energy implies the development of alternative, complementary, and renewable solutions. The idea developed in the present article consists in the use of vortex-induced vibrations to harness energy from low currents. The convertor modulus presented here is composed of an elastically mounted, rigid cylinder on end-springs, undergoing flow-induced motion when exposed to transverse fluid-flow. An experimental prototype was developed and tested in a free-surface water channel and is already able to recover energy with a good efficiency from free-stream velocity from 0.5 to 1 m/s. However, the large number of parameters (linked to automatic control, mechanical design, hydraulic parameters such as velocity of fluid flow) associated with its performance requires optimization. An analytical model is developed in order to accelerate the maximum efficiency determination, which is also estimated as a function of hydrodynamic forces. A complete 2D CFD model solution is then used, on one hand to validate the analytical model and on the other hand to determine lift, drag and added mass coefficients. Optimal control parameters are well estimated by the analytical model and CFD tests reveal a strong influence of high amplitude oscillations on the hydrodynamic coefficients. Highlights: Energy of VIV can be recovered by a hydropower system, but it needs an automatic control to adjust its optimal parameters. An analytical model is used to estimate the optimal parameters with equations depending on hydrodynamic coefficients. The analytical model is validated by a CFD model able to give the hydrodynamic coefficients for large oscillation amplitudes.